2017
DOI: 10.1111/jvec.12248
|View full text |Cite
|
Sign up to set email alerts
|

The mosquito fauna of the western region of Spain with emphasis on ecological factors and the characterization ofCulex pipiensforms

Abstract: This study updates the diversity, distribution, and seasonal trends of mosquitoes in a western region of Spain, assesses ecological determinants of Culex pipiens s.l., and determines form composition of Cx. pipiens s.s. populations. A total of 1,495 mosquitoes of 16 species was collected during 2012-2013, of which Cx. pipiens s.l. and Cx. theileri were the most abundant. Five new records for An. maculipennis s.s., Orthopodomyia pulcripalpis, Aedes (Ochlerotatus) punctor, Cx. europaeus, and Cx. modestus were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 49 publications
4
27
2
Order By: Relevance
“…The strategic location in major migratory bird flyways, the many wetland areas, favourable environmental conditions and a higher density of competent vectors are possible factors implicated in the greater spread of WNV in this area. In this respect, it has been shown that C. pipiens, C. perexiguus, C. theileri and C. modestus are the main Culex species detected in the regions studied here (Aranda et al., ; Bravo‐Barriga et al., ; García‐Bocanegra, Jaén‐Téllez, et al., ; Vázquez et al., ). In other European countries, such as France, seropositivity for WNV in dogs ranged between 6.7% and 8.4% (Davoust et al., ; Maquart et al., ).…”
Section: Discussionmentioning
confidence: 62%
“…The strategic location in major migratory bird flyways, the many wetland areas, favourable environmental conditions and a higher density of competent vectors are possible factors implicated in the greater spread of WNV in this area. In this respect, it has been shown that C. pipiens, C. perexiguus, C. theileri and C. modestus are the main Culex species detected in the regions studied here (Aranda et al., ; Bravo‐Barriga et al., ; García‐Bocanegra, Jaén‐Téllez, et al., ; Vázquez et al., ). In other European countries, such as France, seropositivity for WNV in dogs ranged between 6.7% and 8.4% (Davoust et al., ; Maquart et al., ).…”
Section: Discussionmentioning
confidence: 62%
“…theileri is limited by the temperatures. It was the most abundant species in urban areas, this is in disagreement with its dispersal on the western region of Spain [18]. Monthly activities of this species in Mohr and Darab counties (Fars Province) were reported from April to September [2].…”
Section: Discussionmentioning
confidence: 85%
“…Present evidence, however, suggests that this habitat separation is far less rigid, with cross-breeding experiments and analysis of genetic markers from field and colony specimens indicating that inter-breeding populations of pipiens and molestus can be found sympatrically in both above- and belowground urban habitats, as well as in rural and semi-rural areas [ 100 , 103 , 110 , 114 , 115 , 116 , 117 , 118 , 119 ]. Indeed, natural hybrid pipiens/molestus forms have now been reported from at least 12 European countries ( Figure 2 a) with reported rates of hybridisation of up to 25.7% [ 116 ]. The relative abundance of each of the forms and hybridisation rates have been found to vary across latitudes, with the proportion of molestus populations relative to pipiens increasing from northern to southern latitudes [ 120 ].…”
Section: Introductionmentioning
confidence: 90%
“…References used for the production of maps showing country-level presence of the following species: Culex pipiens ecoform pipiens/ Culex pipiens ecoform molestus hybrids ( Figure 2 a) Austria [ 114 ] Belgium [ 204 ] France [ 102 ]—hybrids reported from a colony strain originally collected in France Germany [ 110 ] Greece [ 119 , 205 ] Italy [ 118 , 120 ] Netherlands [ 100 , 115 , 120 ] Portugal [ 117 , 149 ] Serbia [ 206 ]—methodology used for identification unclear. Spain [ 116 , 147 , 207 ] Sweden [ 120 ] United Kingdom [ 101 , 103 ] Culex pipiens / Culex quinquefasciatus hybrids ( Figure 2 b): Greece [ 102 , 121 ] Culex torrentium ( Figure 3 ) Albania [ 208 ] Austria [ 114 , 209 ] Belarus [ 209 ] Belgium [ 89 , 204 , 210 ] Czech Republic [ 89 ...…”
mentioning
confidence: 99%
See 1 more Smart Citation